Mathematics
rosie777
13

How to simplify y-5=-13/6(X-1) step by step please

+1
(1) Answers
Lara14

[latex]y-5= \frac{-13}{6(x-1)} [/latex] Refine [latex]y-5 = - \frac{13}{6(x-1)} [/latex] Expand [latex]- \frac{13}{6(x-1)} = - \frac{13}{6x-6} [/latex] Multiply both sides by 6 x - 6 (6x-6)y -(6x-6)5 = - (6x-6)[latex] \frac{13}{6x-6} [/latex] Refine: (6x-6)y - (6x-6)5 = 13 6xy - 6y - 30 x + 30 = - 13 6xy - 6y -30x + 30 + 30 x = -13+30x 6xy - 6y + 30 = -13+30x 6xy - 6y +30-30 = - 13 + 30 x -30 6xy - 6y = 30 x - 43 take out y : y(6x-6) = 30 x - 43 Divide both sides by 6x - 6 : [latex] \frac{y(6x-6)}{6x-6} = \frac{30x-43}{6x-6} [/latex] [latex]y = \frac{30x-43}{6x-6} [/latex] hope this helps!

Add answer